Kippinge valfartskirke - Gad, Tue (Religionsvidenskabeligt Tidsskrift, 1984)
The Danish church of Kippinge in Falster is remarkable for being a centre of pilgrimage not only before the Reformation, but well into the 18th century. In spite of official censure, thousands of people went there, and miraculous cures were reported. Manuscript treaties from the 17th century are preserved, in which local clergymen fervently discuss whether that pilgrimage is a pious if unorthodox custom to be tolerated, or whether it is the work of Satan. The *”holy” object in the Middle Ages was a miraculous host; after the Reformation it seems to have been the church itself, but in the 18th century it was the adjoining well, which caused no theological objections.